A comparative study on sperm penetration in estrual mucus and polyacrylamide gel in relation to seminal characteristics - KAUSHAL, GAGANDEEP; PANGAONKAR, G R; VERMA, H K (The Indian Journal of Animal Reproduction, 2023)
l!J. vitro sperm mucus penetration study was done in freshly collected estrual mucus of buffaloes and in synthetic migrationmedia i.e. polyacrylamide gel (2%). Sperm mucus penetration distance was measured as an indicator of fertility . Sperm mucuspenetration distance values have +ve correlation with live and normal sperm count. In polyacrylamide there was +ve correlationbetween sperm penetration distance value and normal sperm count. Polyacrylamide gel can be used successfully as a better substitutepenetration media for sperm penetration for assessing the fertility of the semen.
Keywords: Sperm; estrual; mucus; polyacrylamide; penetration; fertility